Towards new zero-thermal-expansion materials: Li-free quartz solid solutions stuffed with transition metal cations. Issue 4 (April 2023) - Bazzaoui, Haytem; Genevois, Cécile; Véron, Emmanuel; Pitcher, Michael J.; Allix, Mathieu; Zandonà, Alessio
Abstract: Stuffed aluminosilicate quartz solid solutions (Qss) represent the main functional component of state-of-the-art zero-thermal-expansion glass-ceramics. For the first time, we present the synthesis of Li-, Mg- and Zn-free Qss solely stuffed with transition metal cations (Fe 2+, Ni 2+, Co 2+ ); partial Li + co-doping enables also significant Mn 2+ incorporation. They were obtained by glass powder crystallization; Qss crystals exhibit compositionally tunable coefficients of thermal expansion (CTEs), from − 2 × 10 −6 K −1 to ∼10 × 10 −6 K −1 in the range 30–300 °C. Co 2+ -bearing crystals exhibit the closest-to-zero CTE value (0.2 ×10 −6 K −1 ) and the most isotropic behavior in the whole Qss family, opening up new perspectives for the development of Li-free low-expansion materials. From a structural point of view, we identified the unit cell volume (and not the pseudo-hexagonality of the aluminosilicate framework) as the key structural parameter leading to low or negative CTEs in Qss, with a linear correlation extending to non-stuffed non-silicate quartz-like phases.